2023
DOI: 10.3390/ma16072708
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Bond Performance of NC-UHPC Interfaces with Different Roughness and Substrate Strength

Abstract: This paper investigates the bond failure performance between precast normal concrete (NC) and cast-in situ ultra-high performance concrete (UHPC), emphasizing the influence of interfacial roughness. The interfacial bonding behavior under tension and under shear was investigated based on 72 groups of pull-off tests and 36 groups of bi-shear tests, considering six different interface treatment methods and two different NC strength levels. The results demonstrate that certain interfacial roughness is essential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Beushausen et al [26] and Kamada et al [27] investigated the effect of surface moisture on the layer properties, but the experimental results were discrete, and the relationship between wet and dry substrate layer properties was not clear. Roughness significantly increases the dimension bond strength, and higher substrate roughness ensures a larger contact area between the two types of concrete, resulting in a better bond, as evidenced by the results of Zhang et al [28] and Tian et al [29].…”
Section: Introductionmentioning
confidence: 88%
“…Beushausen et al [26] and Kamada et al [27] investigated the effect of surface moisture on the layer properties, but the experimental results were discrete, and the relationship between wet and dry substrate layer properties was not clear. Roughness significantly increases the dimension bond strength, and higher substrate roughness ensures a larger contact area between the two types of concrete, resulting in a better bond, as evidenced by the results of Zhang et al [28] and Tian et al [29].…”
Section: Introductionmentioning
confidence: 88%
“…Besides, reliable interface between UHPC and concrete is crucial to achieve the shared force. The interface bond strength is influenced by various factors, such as surface treatment [ 16 , 17 ], curing conditions [ 18 ], roughness and substrate strength [ 19 ], loading modes and environmental conditions [ 20 ]. Different experimental methods, such as flexural tensile tests, slant shear tests, direct shear tests and splitting tensile tests, can be used to evaluate the interface bond strength and durability.…”
Section: Introductionmentioning
confidence: 99%
“…He Yan et al [36] evaluated the mechanical characteristics of concrete binders and the effects of the interface roughness of new and existing concrete and found that an interface binder significantly improved the strength of new and existing concrete and the bonding strength. Liao Zhaoqian and Wang et al [37,38] used reinforced ordinary concrete with UHPC and performed mechanical property tests. After roughness treatment, the UHPC-NC specimen had better interface bonding performance and greater interface bonding strength than the specimen without roughness.…”
Section: Introductionmentioning
confidence: 99%